Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0143669
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Polyimide Membrane as Cell Carrier for Subretinal Transplantation of Human Embryonic Stem Cell Derived Retinal Pigment Epithelium

Abstract: In this study, we investigated the suitability of ultrathin and porous polyimide (PI) membrane as a carrier for subretinal transplantation of human embryonic stem cell (hESC) -derived retinal pigment epithelial (RPE) cells in rabbits. The in vivo effects of hESC-RPE cells were analyzed by subretinal suspension injection into Royal College of Surgeons (RCS) rats. Rat eyes were analyzed with electroretinography (ERG) and histology. After analyzing the surface and permeability properties of PI, subretinal PI memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 52 publications
0
47
0
1
Order By: Relevance
“…Studies of the mechanical properties of Bruch’s membrane are limited in number, study different layers and use a range of techniques to obtain data, however the elastic modulus appears to be around 2–4 MPa [38]. The substrates used in this study were several orders of magnitude higher than that of Bruch’s membrane, although similar to those used in other studies [7, 35] and in the same order of magnitude as that reported for non-porous PTFE [39]. Furthermore, the differences in surface stiffness resulting from the different surface treatments were relatively small, even across multiple regions on different samples.…”
Section: Discussionmentioning
confidence: 80%
“…Studies of the mechanical properties of Bruch’s membrane are limited in number, study different layers and use a range of techniques to obtain data, however the elastic modulus appears to be around 2–4 MPa [38]. The substrates used in this study were several orders of magnitude higher than that of Bruch’s membrane, although similar to those used in other studies [7, 35] and in the same order of magnitude as that reported for non-porous PTFE [39]. Furthermore, the differences in surface stiffness resulting from the different surface treatments were relatively small, even across multiple regions on different samples.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the surgical difficulties and putative immunologic response to the transplant, implantation of sheets of hESC-RPE with or without a supportive biomatrix may be more efficient in repopulating areas with more extensive damage to the outer neuroretina/RPE/Bruch's membrane complex. 9,27,28 However, preclinical results in large-eyed animals suggest that caution is warranted, as such constructs may cause outer retinal atrophy. 10,28 Therefore, it would be important to optimize this technology, if successful integration of hESC-RPE is to be achieved in areas of extensive atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…9,27,28 However, preclinical results in large-eyed animals suggest that caution is warranted, as such constructs may cause outer retinal atrophy. 10,28 Therefore, it would be important to optimize this technology, if successful integration of hESC-RPE is to be achieved in areas of extensive atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous stem cells require individual cell isolation and characterization, whereas allogeneic stem cells can be produced in a time‐ and cost‐effective way. Allogeneic stem cells are advantageous in the sense that a sufficient number of cells with a high biological activity can be secured from a healthy donor over a short time period for the storage and production of therapeutic agents . Therefore, they can be effectively used to treat acute diseases, such as stroke or acute GVHD …”
Section: Introductionmentioning
confidence: 99%